Genetic diversity and risk factor analysis of drug-resistant Escherichia coli recovered from broiler chicken farms. (February 2023) - Bhargavi, Dadimi; Sahu, Radhakrishna; Nishanth, Maria Anto Dani; Doijad, Swapnil Prakash; Niveditha, Pollumahanti; Kumar, Obli Rajendran Vinodh; Sunanda, C.; Girish, P.S.; Naveena, B.M.; Vergis, Jess; Malik, Satya Veer Singh; Kurkure, Nitin Vasantrao; et al.
Abstract: A total of 38 Escherichia coli isolates were recovered from 120 samples collected from various sources of broiler chicken farms (n = 10 each) in Andhra Pradesh and Telangana states. Though the recovered E. coli isolates were found variably resistant to the tested antibiotics, all the tested isolates were susceptible to meropenem. Alarming multi-drug resistance (MDR) was observed (34/38) among the recovered isolates, wherein antibiotic-resistant genes ( bla TEM, bla SHV, and tet A) were detected, except for bla CTX-M-9 . The heatmap with cluster analysis exhibited that majority of the E. coli isolates recovered from different sources and regions clustered together based on their phenotypic resistance suggesting co-sharing of resistance. However, the pulsed-field gel electrophoresis (PFGE) typing revealed an extremely diverse genotypic profile. Further, a significant statistical association was not observed between hypothesized risk factors and recovered MDR- E. coli isolates from various sources, although a significant statistical association between antibiotic resistance with large flock size, poor biosecurity practices, poor workers' hygiene, and poor disinfection practices was noticed. Since the study highlighted an alarming level of drug resistance among the recovered E. coli isolates, further in-depth research in similar veins is required to ensure the prudent use of antimicrobials in the poultry sector and the implementation of an antimicrobial surveillance system. Highlights: E. coli isolates from broiler chicken farms exhibited alarming MDR profile. E. coli isolates harbored tet A, bla TEM, bla SHV genes. Majority of the isolates clustered together suggesting co-sharing of resistance. PFGE pattern exhibited extremely diverse genotypic profile. In-depth risk analysis is warranted to ensure prudent use of antimicrobials in poultry.